2017
DOI: 10.1080/10717544.2017.1378937
|View full text |Cite
|
Sign up to set email alerts
|

Which inhaled corticosteroid and long-acting β-agonist combination is better in patients with moderate-to-severe asthma, a dry powder inhaler or a pressurized metered-dose inhaler?

Abstract: Two main types of devices are used to facilitate the administration of inhaled corticosteroid (ICS) and long-acting β-agonist (LABA) in combination, dry powder inhalers (DPIs) and pressurized metered-dose inhalers (pMDIs). There are few reports comparing the effects of the two devices, and it is unknown which should be recommended for asthma patients with given sets of characteristics. In the current study, the beneficial effects and side effects associated with DPIs and pMDIs were compared, and the question o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Patient outcomes are directly linked to treatment success and restricting access to some treatment options has potentially detrimental effects on the quality of care that patients receive and their subsequent outcomes. 16 17 26 27 Indeed, patient preference, adherence and inhalation technique are important closely inter-related determinants of clinical outcomes. As such, they may also influence healthcare costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient outcomes are directly linked to treatment success and restricting access to some treatment options has potentially detrimental effects on the quality of care that patients receive and their subsequent outcomes. 16 17 26 27 Indeed, patient preference, adherence and inhalation technique are important closely inter-related determinants of clinical outcomes. As such, they may also influence healthcare costs.…”
Section: Discussionmentioning
confidence: 99%
“…15 However, changing inhaler class has important implications for patients, since pMDIs are more suitable for many patients because of, for example, inhaler type, insufficient inspiratory flow rate, or handling capabilities and individual preference. 16 Moreover, switching from pMDIs to DPIs could have other environmental impacts, including human toxicity, marine eutrophication and fossil depletion. 8 Therefore, there is an unmet need to ensure that patients continue to receive the most effective and appropriate treatment while also reducing the negative impact of inhalers on the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Patient preference is important in achieving effective treatment and many patients prefer pMDIs. In a non-industry funded study comparing the same drug given to patients with asthma as either a pMDI or as a DPI, nearly double the number of patients (∼60%) preferred the pMDI device compared to the DPI (∼35%) [10]. Evidence on the error rates that patients have using the different inhaler devices in routine daily use is conflicting, with no convincing evidence for the superiority of any one device type over another.…”
Section: What Is the Association Between Inhaler Propellants And Globmentioning
confidence: 99%
“…For example, despite the high DPI usage, a recent study reported that Japanese patients may still prefer a pMDI to a DPI. 27 Furthermore, there are clearly local factors which can influence prescriber choice, given that the proportion of inhaler doses (excluding nebulized) given by pMDI ranges from 34% in Japan to 88% in the US ( Figure 5 ). Differing health policies, costs, health insurance issues, commercial aspects and prescribers’ and patients’ preferences can cause significant variation in prescribing practice, even within the European Union.…”
Section: The Role Of Pmdis In Clinical Practicementioning
confidence: 99%